FLORISTIC COMPOSITION AND STRUCTURE OF SUBALPINE SUMMIT HABITATS ON MT. GEDE-PANGRANGO COMPLEX, CIBODAS BIOSPHERE RESERVE, WEST JAVA, INDONESIA - Asep Sadili; Kuswata Kartawinata; Abdulrokhman Kartonegoro; Herwarsono Soedjito; Alex Sumadijaya (BRIN Publishing (Penerbit BRIN), 2009)
SADILI, A., KARTAWINATA, K., KARTONEGORO, A., SOEDJITO, H. & SUMADIJAYA, A. 2009. Structure and composition of subalpine summit habitats on Mt. Gede-Pangrango complex, Cibodas Biosphere Reserve, West Java, Indonesia. Reinwardtia 12 (5): 391–404. We undertook a phytosociological analysis of the subalpine herbaceous and shrubby vegetation at the Mandalawangi and Suryakencana meadows and the scrub at the Crater Side at the tops of Mt. Gede and Mt. Pangrango in the Cibodas Biosphere Reserve. We recorded 30 species of 18 families of saplings, shrubs, seedlings and herbs in 78 quadrats with a total area of 7,800 m2. Anaphalis javanica, a woody tall herb and long-lived pioneer was the dominant species in the sapling and shrub stratum, while Isachne pangerangensis, Tripogon exiguus and Carex verticillata were prevalent in the seedling and herb stratum at Mandalawangi and Suryakencana. Stunted shrub is Vaccinium varingaeifolium, dominant in the Crater Side scrub. Based on the importance values, the Mandalawangi meadow may be designated as the Anaphalis javanica-Isachne pangerangensis community type, the Suryakencana meadow as Anaphalis javanica-Tripogon exiguus community type and the Crater Side scrub as Vaccinium varingiaefolium-Seliguea feei community type. The similarity indices between Mandalawangi and Suryakencana community types were very high (>75 %) while those between the Crater Side and Mandalawangi and the Crater Side and Suryakencana were very low (